The Secrets of the Dark Continent - Yannis Grammatopoulos (The European Journal of Psychoanalysis, 2018)
The present paper discusses the reasons for the termination of the psychoanalytic treatment of a neurotic woman. The patient presented early enough the layout of a hysterical neurosis, built around the question of femininity, for posing which various triangles were created. When jouissance drew the patient to the side of repetition, a psychoanalytic act brought her back to working-through inside transference. The dreams that followed this act led to the emergence of an element that revolved around the mark of femininity on the body, which was linked to the jouissance of the not-whole and thus lied beyond the structure of hysterical desire. This time the analyst failed to encapsulate this element in transference, due to his mistaken attempt at one more interpretation at the phallic level. Consequently, like Freud’s famous case study of Dora, the patient decided to end the treatment. This failure is discussed with regards to Freud’s analysis of Dora and the dream of Irma’s injection, and Lacan’s views on them.
Keywords: Dora; Dream of Irma’s injection; femininity; hysteria; Jouissance of not-whole